CLINICAL STUDY OF AC-4-AN AYURVEDIC COMPOUND PREPARATION AS AN ORAL CONTRACEPTIVE - Gowri, N. (Medknow Publications & Media Pvt Ltd, 1982)
In this paper the contraceptive effect of Ayush AC-4 an ayurvedic compound preparation is assessed. Totally 281 volunteers have been enrolled in the study. Tho menstrual cycles covered by the women ranged from 1-30. Tho result is moderately satisfactory. No toxic symptoms or severe aide-effects were noticed. The authors say that in tho light of the results obtained in this study, it may be desirable and feasible to make this compound preparation acceptablo like the other oral contraceptives